Investigation of the potential biomass waste source for biocoke production in Indonesia : A review - Gani, Asri; Erdiwansyah, E.; Munawar, Edi; Mahidin, M.; Rizalman, Mamat; S. M., Rosdi (Elsevier Ltd, 2023)
Using biomass waste for renewable energy and sustainable fuel production has gained significant attention recently. This review investigates the potential biomass waste sources for biocoke production in Indonesia. Biocoke, a form of solid fuel derived from biomass, has emerged as a viable alternative to traditional coke in various industrial applications, including steelmaking. This review comprehensively analysed available literature and data sources to identify Indonesia's most abundant and suitable biomass waste sources. The assessment considered biomass availability, sustainability, energy content, and compatibility with biocoke production processes. The environmental impacts associated with the production and utilization of biocoke were also considered. The findings reveal that Indonesia possesses a rich diversity of biomass waste sources with a high potential for biocoke production. Agricultural residues, such as rice straw, corn stalks, and palm oil residues, are identified as promising feedstocks due to their abundance and availability throughout the country. Moreover, biomass waste can contribute to waste management and alleviate environmental concerns associated with open burning and landfilling. The review also highlights the importance of sustainable practices in biomass waste collection and processing. Efficient collection and logistics systems and advanced biomass conversion technologies are crucial to ensure biocoke production's economic viability and environmental sustainability. Furthermore, the economic viability of biocoke production is examined by considering factors such as feedstock costs, energy efficiency, and market demand. The potential challenges and barriers, including technological, regulatory, and market-related aspects, are also discussed to provide a comprehensive overview of the feasibility of large-scale biocoke production in Indonesia. Overall, this review underscores the significant potential of biomass waste as a valuable resource for biocoke production in Indonesia. By harnessing the abundant biomass waste streams available in the country, Indonesia can reduce dependence on fossil fuels, mitigate greenhouse gas emissions, and promote sustainable development in the energy sector.